Does Insurance Sector Matter for Economic Complexity? - Folorunsho M. Ajide; Tolulope T. Osinubi; Titus A. Ojeyinka (Organizations and Markets in Emerging Economies, 2023)
The study examines the impact of the insurance market on economic complexity in 28 OECD nations within a period of 1995–2020. The study also examines whether the impact of life insurance on economic complexity would be different from that of the non-life insurance sector within the insurance market. The results based on pooled mean group (PMG) estimators reveal that the insurance sector influences economic complexity positively. This finding is further substantiated after employing panel co-integrating regression and method of moment quantile regression (MM-QR). The study concludes that the insurance sector is a key instrument in upgrading the economic complexity of an economy. Since the distributional impact of economic complexity also depends on economic and financial risk, the insurance sector can assist in mitigating the risks and uphold the productive knowledge structure needed to enhance national product sophistication.